Experimental and numerical investigation of self-priming siphon side weir on a straight open channel - Aydin, M. Cihan; Ozturk, Mualla; Yucel, Ahmet (Elsevier Sci Ltd, 2015)
Siphons are basic and powerful hydraulic instruments which can be used as dam spillway or weir. In a siphon, atmospheric pressure pushes the water into the region of vacuum at the crest of the siphon, and then water falls towards the outlet of siphon. In this study, the siphon used as a side weir was investigated to determine hydrodynamic characteristics experimentally, theoretically and numerically. First, the flow properties of main channel were examined for subcritical flow condition. Then, the velocity and pressures distributions inside the siphon; finally the discharge performance of siphon side weir was determined comparatively, and the results were discussed. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Siphon; Side weir; CFD analysis; Physical model; Numerical model; Free surface flow